Effect of Polyester Fiber on Air Voids and Low-Temperature Crack Resistance of Permeable Asphalt Mixture - Jin-rong Wu; Fei Li; Qin-yong Ma (Advances in Civil Engineering)
With the rapid development of asphalt pavement, the drainage capacity of asphalt pavement is becoming more and more demanding. Therefore, it is imperative to study the permeable asphalt mixture. The air voids and the connected air voids are the main factors affecting the drainage function and low-temperature performance of asphalt pavement. In order to solve the drainage and low-temperature cracking problem, it is proposed to incorporate a certain amount of polyester fiber into the permeable asphalt mixture. This paper studies the air voids and low-temperature performance of asphalt mixture with different polyester fiber contents. It is concluded that with the increase of polyester fiber content, both the air voids and the connected air voids decrease first and then increase and reach the minimum value when the polyester fiber content is 0.4%. At this time, the low-temperature crack resistance of the permeable polyester fiber asphalt mixture is also the best.